Application of immunocytochemistry to the diagnosis of primary epithelioid angiosarcoma of the lung - Kuroda, Naoto; Hamaguchi, Nobumasa; Inoue, Kaori; Ohara, Masahiko; Mizuno, Keiko; Hayashi, Yoshihiro; Lee, Gang-Hong (Medical molecular morphology, 2009)
Pulmonary epithelioid angiosarcoma is rare, and there are no descriptions of the immunocytochemistry of such a case. We report a case with focus on immunocytochemistry of imprint cytological specimens here. A 43-year-old Japanese man presented with cough. Brushing cytology of the tumor using a bronchoscope showed a malignant neoplasm. Subsequently, left lower lobectomy was undertaken. Imprint cytological material of the neoplastic cells noted some clusters of round, or oval, to polygonal epithelioid cells. Histological examination showed the proliferation of epithelioid neoplastic cells containing erythrocytes in the cytoplasm. The immunocytochemistry in imprint cytological specimens showed a focal positive reaction for von Willebrand factor, and the immunohistochemistry of the surgically resected lung tumor showed a focal positive reaction for Fli-1, von Willebrand factor, CD31, and CD34. Finally, we suggest that the immunocytochemical study of imprint cytological materials may supply available information in diagnosing angiosarcoma with epithelioid features lacking characteristic structures.